Device Onboarding Using FDO and the Untrusted Installer Model. - Cooper, Geoffrey H. (Communications of the ACM, 2024)
The Internet of Things (IoT) market has expanded significantly, encompassing various sectors like home, retail, manufacturing, and transportation, with millions of devices and servers dedicated to monitoring real-world aspects. Regardless of the field, all IoT devices share the characteristic of transitioning from initial ownership to target application ownership to fulfill their intended functions, a process known as onboarding, which requires fast, reliable, and secure interaction between devices and servers. Two distinct approaches to onboarding, trusted and untrusted installers, exist, with trusted installers employing configurator tools to establish trust between devices and servers, while untrusted installers rely on mechanisms like ownership vouchers for authentication, offering scalability and parallel device onboarding.